Total hip arthroplasty: Evolution of the use of dual mobility cups in Lebanon - Assi, Chahine (2018)
Recurrent dislocation, being a major reason for revision total hip arthroplasty (THA), was found to decrease significantly using dual mobility cup (DMC) compared to standard cups (SC), and that in both primary and revision THA. These acetabular implants have gained popularity in recent years in different countries besides the country of original concept, France. In Lebanon, the number of DMC implants witnessed a raise but with a lack of quantified reports. Having no national registry, we conducted a series of investigations with each registered company providing THA implants on the Lebanese territory. Data collection was obtained over 5 years, from 2013 to 2017. Data analysis was conducted for each year in terms of rates of implanted THA with DMC (THA-DMC) and those with SC (THA-SC). Out of the total THA number per year, the percentage of THA-DMC implanted in Lebanon shifted from 34.95% in 2013 to 61.3% in 2017 (z = 17.8; p = 0.0001), yielding a relative increasing rate of 88% over a 5-year period span. Additionally, the rate increase has been steady and linear from 2013 to 2017. Orthopedic surgeons in Lebanon seem to favor DMC over SC in THA surgeries. While this trend has been unsurprisingly noted in France, and in many European countries, no accurate data has been reported on DMC prevalence use from the French literature. When compared to DMC use in the United States (US), the DMC rate of 61.3% in Lebanon was found to be much higher than the reported 17% from US joint replacement registry.The reported reduced dislocation and mechanical loosening rates following DMC could be the reason behind the observed DMC popularity in Lebanon